The effects of employer compensation, liquidity management, and employee productivity on profitability: the failed case of Washington Mutual - Ljubenko, Bojan, author; Chermack, Thomas J., advisor; Mumford, Troy V., committee member; Korte, Russell, committee member; Venneberg, Donald L., committee member (Colorado State University. Libraries, 2016)
The purpose of this study was to determine if the effects of three variables—employee productivity, liquidity management, and employee compensation—on employer's profitability performance might have predicted the 2008 organizational failure of Washington Mutual Bank. Researchers have noted that human expertise (that is, people and their skills) is the most important element of organizational strategy. In this study, salaries and employee benefits were used to measure employee compensation. Total loans to assets ratio was used to measure bank liquidity. Return on average asset was used to measure bank profitability. In addition, the human capital return on investment ratio was used to measure employee productivity. The purpose of this study was to investigate the extent to which the three variables could predict bank performance and ultimately, bank failure. To investigate these relationships, historical data for Washington Mutual Bank were selected from the Federal Deposit Insurance Corporation (FDIC) database and compared to standard data from the FDIC's peer banks. The study’s findings indicated that WaMu's return on human capital correlated with the return on average profitability. In the FDIC standard peer group data, both the salaries and employee benefits and total loans to assets variables correlated with return on average profitability.